A Model to Describe the Magnetomechanical Behavior of Martensite in Magnetic Shape Memory Alloy - Zaoyang Guo; Haitao Li; Qiang Wan; Xianghe Peng; Jing Wen (Advances in Condensed Matter Physics)
A model to describe the constitutive behavior of magnetic shape memory alloy composed with pure martensite is proposed based on the analysis of variants reorientation. A hyperbolic tangent expression is given to describe the variants transition during magnetic and mechanical loading process. The main features of magnetic shape memory alloy, such as pseudoelastic and partially pseudoelastic behavior as well as minor hysteretic loops, can be successfully replicated with the proposed model. A good agreement is achieved between calculated results and experimental data for NiMnGa single crystal.